IMPORTANT INFORMATION ABOUT ALISHER NAVOI'S WORK (American Journal of Interdisciplinary Research and Development, 2024)
In this verse of Hazrat Navoi praises many qualities of Allah: kindness, power, forgiveness, mercy. The verse is also remarkably artistic. In the course of the analysis, we came across many unique and beautiful examples of art, including: tasbeh, tanosub, tazod, rhymes. Like other works of Navoi, this verse has passed through the centuries and has not lost its value to this day.